Biomechanics of extra-alveolar mini-implants - Marcio R. Almeida
ABSTRACT It is undeniable that extra-alveolar mini-implants anchorage has revolutionized Orthodontics. Correspondingly, the proper understanding of mini-implants biomechanics allowed to broaden the range of dental movements as never seen before in clinical practice. However, in order to produce better treatments, especially regarding the effects in occlusal plane, it is important to be aware of the numerous possibilities of applying force systems based on skeletal anchorage. Thus, this paper aims to address, by means of clinical cases, the application of biomechanics concepts that are extremely relevant to the proper employment of extra-alveolar mini-implants.